Panonychus citri (MacGregor) (Tetranychidae) and Eriophyes medicaginis K. (Eriophyidae): Two important phytophagous mites recorded for the first time in Greece - Emmanouel, N.G.; Papadoulis, G.TH. (ENTOMOLOGIA HELLENICA, 1987)
Panonychus cirri (MacGregor) one of the most important phytophagous mites in many parts of the world, has been collected from citrus trees in various localities of county Preveza, Heperos, Greece. This mite has been, possibly, introduced to Greece via Albania. Another phytophagous mite, Eriophyes medicaginis Keifer, well known to cause witches’ broom on alfalfa, has been collected from Medicago saliva L. in the counties Attiki and Boiotia of central Greece. In a two year study on arthropods associated with alfalfa at the Kopafs region of Boiotia, E. medicaginis was found to be constant and recedent in both years. High population densities were observed during the period mid-September to mid-March.